2011
DOI: 10.1186/cc10374
|View full text |Cite
|
Sign up to set email alerts
|

Yale insulin protocol infusion in sepsis patients

Abstract: Introduction Fibrinolytic shutdown plays a pivotalrole in the pathogenesis of multiple organ dysfunction syndrome (MODS) in disseminated intravascular coagulation (DIC). We tested the hypothesis that the levels of thrombin activatable fi brinolysis inhibitor (TAFI) are not suffi cient to overcome fi brinolytic shutdown, thus contributing to MODS and the poor prognosis in sepsis-induced DIC. Methods Fifty patients with sepsis, severe sepsis, or septic shock were enrolled in the study. The DIC was diagnosed base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…15 These favorable results were likewise reported in centers in Brazil, Portugal and the US. [16][17][18] In our study, a substantial number of protocol deviations occurred. The most frequent deviation was on improper insulin dose adjustment followed by improper timing of BG checks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 These favorable results were likewise reported in centers in Brazil, Portugal and the US. [16][17][18] In our study, a substantial number of protocol deviations occurred. The most frequent deviation was on improper insulin dose adjustment followed by improper timing of BG checks.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] In the study of Tamaki, et al, conducted in Japan, a cohort of 40 cardiac surgery patients were compared to a historical cohort of 35 patients.…”
Section: Discussionmentioning
confidence: 99%
“…44 Multiple other protocols have been developed with varying accuracy, perhaps one of the most widely used is the Yale protocol. 45 A study that compared the Yale protocol to the protocol used in the Leuven studies revealed that patients treated under the Yale protocol had better than average glucose control with less hypoglycemic events. 46 However, a major drawback of using protocols for glucose control is that it requires a large time commitment from clinical staff and is associated with increased costs.…”
Section: Protocolsmentioning
confidence: 99%